Effect Size : STEM pada Pembelajaran IPA Terhadap Keterampilan Abad 21 - Raudhatul Jannah; Lufri Lufri; Asrizal Asrizal; Sandijal Putra Putra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The study used a meta-analysis with the aim of measuring the effect of STEM on science learning on 21st century skills. The number of articles obtained in this study was 25 articles. These results show that 1), the STEM approach to 21st century skills is very effective for students. 2), the level of education, STEM has a high effectiveness on 21st century skills. 3), the use of learning models in STEM is effective for 21st century skills. So it is concluded that STEM in IPA learning against 21st century students' skills is effectively used